1953
DOI: 10.1103/physrev.90.921
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Chamber Observations of the Heavy Charged Unstable Particles in Cosmic Rays

Abstract: In a series of pictures taken with a multiplate cloud chamber, we have observed a number of charged unstable particles considerably heavier than 7r-mesons, of which some decay at rest (S particles) and some decay in flight (V ± particles). In each case the charged decay product is a particle of mesonic mass. From our results, which are not yet completely conclusive, it appears that most of the observed events can be explained by the two-body decay of a single kind of particle. The evidence concerning the mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1953
1953
1959
1959

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus have photographed a decay in which both secondary particles penetrated several lead plates and then each produced a small nuclear interaction : this unusual photograph is reproduced in Plate VI and shows conclusively that both the secondaries are nuclear interacting particles. Bridge et al (1953 a) have reported a value of (163 i 40) gcm-2 of lead for the interaction length for the secondaries of Vo-particles. Clearly the secondaries could be protons or n-mesons, but the accuracy of this measurement is such that it is impossible to exclude a small fraction of p-mesons or other non-interacting particles.…”
Section: Penetration Of the Secondary Particles Through Mattermentioning
confidence: 99%
See 3 more Smart Citations
“…Thus have photographed a decay in which both secondary particles penetrated several lead plates and then each produced a small nuclear interaction : this unusual photograph is reproduced in Plate VI and shows conclusively that both the secondaries are nuclear interacting particles. Bridge et al (1953 a) have reported a value of (163 i 40) gcm-2 of lead for the interaction length for the secondaries of Vo-particles. Clearly the secondaries could be protons or n-mesons, but the accuracy of this measurement is such that it is impossible to exclude a small fraction of p-mesons or other non-interacting particles.…”
Section: Penetration Of the Secondary Particles Through Mattermentioning
confidence: 99%
“…Recently Bridge et al (1953 a) have made a number of Q-value measurements on low-energy VIo-particles using data obtained in their multiplate chamber. and d2 (see fig.…”
Section: Pasadena Datamentioning
confidence: 99%
See 2 more Smart Citations